Social Work in Switzerland - Moergen, Rebecca; Vogel Campanello, Margot (Pedagogika Społeczna Nova, 2023)
What form does Social Work take in Switzerland, and what are the current discourses? This article aims to trace academic and political developments in the analysis of coercive care in Switzerland. In a spirit of scientific self-observation, it will also reflect critically on the role of Social Work as a force of normalization and of the imposition of norms, as well as contextualizing it within current discourses. Looking back into the past makes it possible to expose arbitrary welfare practices that have violated people’s integrity; at the same time, it can reveal processes of professionalization and, linked with these, the development of work methods. The problems confronting Social Work have to do with the tension self-determination and external control, and interventions in the lives of those affected require a particularly high level of legitimation.